2021
DOI: 10.3390/cancers13030560
|View full text |Cite
|
Sign up to set email alerts
|

89Zr-Labeled Domain II-Specific scFv-Fc ImmunoPET Probe for Imaging Epidermal Growth Factor Receptor In Vivo

Abstract: Epidermal growth factor receptor I (EGFR) is overexpressed in many cancers. The extracellular domain of EGFR has four binding epitopes (domains I- IV). All clinically approved anti-EGFR antibodies bind to domain III. Imaging agents that bind to domains other than domain III of EGFR are needed for accurate quantification of EGFR, patient selection for anti-EGFR therapeutics and monitoring of response to therapies. We recently developed a domain II-specific antibody fragment 8709. In this study, we have evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Incucyte live cell imaging S3 (Essen BioScience, Ann Arbor, MI, USA) was used to study the internalization of the DFO-M16Ab in MUC16-expressing OVCAR3 and SW1990 cells and MUC-16-negative SKOV3 cells as previously reported [ref]. Following live-cell imaging, the mean red object area (µm 2 /well) was calculated using the IncuCyte software, which is used to quantify the internalization uptake of the antibody [29].…”
Section: Antibody Internalizationmentioning
confidence: 99%
“…Incucyte live cell imaging S3 (Essen BioScience, Ann Arbor, MI, USA) was used to study the internalization of the DFO-M16Ab in MUC16-expressing OVCAR3 and SW1990 cells and MUC-16-negative SKOV3 cells as previously reported [ref]. Following live-cell imaging, the mean red object area (µm 2 /well) was calculated using the IncuCyte software, which is used to quantify the internalization uptake of the antibody [29].…”
Section: Antibody Internalizationmentioning
confidence: 99%
“…[ 89 Zr]­Zr-oxalate in 1.0 M oxalic acid was purchased from the Saskatchewan Centre for Cyclotron Sciences (SCCS, operated by the Sylvia Fedoruk Canadian Centre for Nuclear Innovation) on the University of Saskatchewan campus. The apparent molar activity of the [ 89 Zr]­Zr-oxalate produced routinely by the SCCS (as used for this study) was found to be in the range of 673–1161 MBq/μmol, by using a method from Holland et al , Purity was determined to be 99.99% . For radiolabeling of the immunoconjugates, the required amount of the [ 89 Zr]­Zr 4+ (in 1.0 M oxalic acid) was neutralized to pH 6.8–7.2 by using sodium carbonate (1.0 M) and the reactions were performed in HEPES buffer (0.5 M, pH 7).…”
Section: Methodsmentioning
confidence: 98%
“…[ 89 Zr]Zr-oxalate was obtained from Saskatchewan Centre for Cyclotron Sciences (SCCS) on the University of Saskatchewan campus and was delivered purified in a minimum volume of 1 M oxalic acid. The apparent molar activity of the [ 89 Zr]Zr-oxalate produced routinely in SCCS (as used for this study), was found to be in the range of 673−1161 MBq/μmol, using a method adapted from Holland et al, 45,46 and radionuclidic purity was determined to be 99.99%. 47 Warning statement: zirconium-89 is a radionuclide that emits potentially hazardous ionizing radiation (gamma rays, positrons) and requires substantial infrastructure (e.g., lead shielding, detectors, radioactive waste storage), radiation safety training, and radiochemistry training to safely handle.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…[ 89 Zr]­Zr-oxalate was obtained from Saskatchewan Centre for Cyclotron Sciences (SCCS) on the University of Saskatchewan campus and was delivered purified in a minimum volume of 1 M oxalic acid. The apparent molar activity of the [ 89 Zr]­Zr-oxalate produced routinely in SCCS (as used for this study), was found to be in the range of 673–1161 MBq/μmol, using a method adapted from Holland et al, , and radionuclidic purity was determined to be 99.99% …”
Section: Methodsmentioning
confidence: 99%